Combined anti-S1 and anti-S2 antibodies from hybrid immunity elicit potent cross-variant ADCC against SARS-CoV-2 - Michael D. Grant; Kirsten Bentley; Ceri A. Fielding; Keeley M. Hatfield; Danielle P. Ings; Debbie Harnum; Eddie C.Y. Wang; Richard J. Stanton; Kayla A. Holder (JCI Insight, 2023)
Antibodies capable of neutralizing SARS-CoV-2 are well studied, but Fc receptor–dependent antibody activities that can also significantly impact the course of infection have not been studied in such depth. Since most SARS-CoV-2 vaccines induce only anti-spike antibodies, here we investigated spike-specific antibody-dependent cellular cytotoxicity (ADCC). Vaccination produced antibodies that weakly induced ADCC; however, antibodies from individuals who were infected prior to vaccination (hybrid immunity) elicited strong anti-spike ADCC. Quantitative and qualitative aspects of humoral immunity contributed to this capability, with infection skewing IgG antibody production toward S2, vaccination skewing toward S1, and hybrid immunity evoking strong responses against both domains. A combination of antibodies targeting both spike domains support strong antibody-dependent NK cell activation, with 3 regions of antibody reactivity outside the receptor-binding domain (RBD) corresponding with potent anti-spike ADCC. Consequently, ADCC induced by hybrid immunity with ancestral antigen was conserved against variants containing neutralization escape mutations in the RBD. Induction of antibodies recognizing a broad range of spike epitopes and eliciting strong and durable ADCC may partially explain why hybrid immunity provides superior protection against infection and disease compared with vaccination alone, and it demonstrates that spike-only subunit vaccines would benefit from strategies that induce combined anti-S1 and anti-S2 antibody responses.